Manajemen Kurikulum dan Pembelajaran Keterampilan Komputer dan Pengolahan Informasi Untuk Membentuk Kemandirian Peserta Didik di Sekolah Menengah Kejuruan - Kawiyono, Aris (Jurnal Varidika: Varia Pendidikan, 2014)
The objectives of this research me to describe (1) the basic formation of KKPI curriculum to establish the independence of learners, (2) preparatory of KKPI curriculum to establish the independence of the learner, (3) teacher preparation of KKPI to establish the independence of learners, (4) the learning implementation of KKPI lessons to establish the independence of learners, (5) evaluation of KKPI curriculum to establish the independence of learners. This qualitative research is conducted in SMK N 1 Donorojo Pacitan. Data collection techniques used observation, interview and documentation. The results of this research were (1) Basic formation of KKPI curriculum at SMK N 1 Donorojo consist ing 5 foundations juridical, philosophical, sociological, psychopedagogical and science and technology. (2) Preparation of KKPI curriculum begins with the manufactured KKPI curriculum. (3) Teachersâ preparation in the formation of learners independence through KKPI learning is to increase its competence by following the activities such as seminars or education and training. (4) Implementation of KKPI learning in SMK N 1 Donorojo already refers to the components of learning. (5) Curriculum evaluation is performed to determine the suitability of the curriculum created prior to its implementation in the field.